Enhancing Image Data Security: DNA Cryptography and XOR-Based Feistel Encryption - Dhakal, Madhav; Shakya, Subarna (Journal of Innovative Image Processing, 2025)
This research aims to generate a robust encryption technique for grayscale images with the integration of Deoxyribonucleic acid (DNA) based computing and mathematical logical XOR operations. It addresses the challenges of securing high-dimensional image data during transmission. In this work, the first layer is based on the Feistel structure concept with logical XOR operations to enhance security, while the second layer utilizes the central dogma, translating pixel data into DNA nucleotides and performing transcription and translation processes to further transform the image. The permutation box, dynamically generated and based on the input image’s data, ensures increased randomness and resistance to key-guessing attacks. The method divides the original image into same-size blocks, performs XOR operations with the key, and transforms the data into a ciphertext image using DNA cryptography principles. Experimental result shows that the proposed scheme achieves better performance, improves the randomness of ciphertext image, and enhances resilience against differential attack, statistical attack, and noise attack, making it a robust solution for secure image data transmission.
Keywords: Data Security; DNA; Digital Image Data; Encryption; Decryption